ISLAMIC SPIRITUAL GUIDANCE MODEL FOR STRENGTHENING THE MORAL CHARACTER OF INMATES IN CLASS IIB PADANGSIDIMPUAN CORRECTION - Nur Aliya Harahap; Armyn Hasibuan; Suci Rahmadani Batubara; Mei Lusi Handayani Nasution; Aisyah Simamora; Cindy Aulia Harahap (PT. Jurnal Center Indonesia Publisher, 2026)
This research aims to determine the Islamic spiritual guidance model in strengthening the morals of inmates at the Padangsidimpuan Class IIB Correctional Institution. This research is motivated by the importance of religious formation as an effort to shape changes in behavior, spiritual awareness and morals of inmates while serving their sentence. The research method used is qualitative research with a descriptive approach. Data was obtained through observation, interviews and documentation of development officers, spiritual mentors and inmates. The research results show that the Islamic spiritual guidance model is implemented through religious lectures, learning to read the Koran, Islamic studies, congregational prayers, dhikr, and daily moral development. Guidanceis carried out on a scheduled basis and involves cooperation between correctional institutions and religious leaders. Islamic spiritual guidance has a positive influence on changes in the attitudes and behavior of inmates, such as increasing discipline, awareness of worship, mutual respect, and decreasing deviant behavior in the correctional environment. Supporting factors in implementing this program include support from officers and enthusiasm of the inmates, while inhibiting factors are limited facilities and a lack of spiritual mentors.